Analysis Of Factors That Influence Individual Taxpayer Compliance In Jombang Regency - Aliza Karima; Muslimin Muslimin; Sofie Yunida Putri (UNIVED Press, 2024)
The purpose of this study is to analyze the various factors that influence individual taxpayer compliance individual taxpayers in Jombang Regency. Understanding of tax regulations, WPOP awareness, suitability of tax rates, use of tax applications, and service quality are some of the factors that this study examined their influence on individual taxpayers compliance in Jombang Regency, which is the subject of this study. All individual taxpayers registered with the Jombang Primary Tax Service Office are the population in this study. The sampling strategy used is a simple random sampling of each taxpayer with a taxpayer identification number (Nomor Pokok Wajib Pajak - NPWP). The test was conducted on 100 respondents obtained from calculating the Slovin formula in determining the research sample. This study uses Partial Least Squares (PLS) as a statistical testing tool. Based on the results of the study, understanding of tax regulations does not influence individual taxpayers compliance; individual taxpayer's awareness influences individual taxpayer's compliance; suitability of tax rates influences individual taxpayer compliance; use of tax applications does not influence individual taxpayers compliance; and service quality influences individual taxpayers compliance.